Nominee Land Sale and Purchase Practices Between Indonesian Citizens and Indonesian Descendants in Yogyakarta (Study of Yogyakarta High Court Decision Number 67/Pdt.G/2021/Pt.Yy) - Gutama, Antonius; Niravita, Aprilia (Semarang State University Undergraduate Law and Society Review, 2025)
The prohibition on land ownership with ownership rights status for non-indigenous Indonesian citizens has resulted in many nominee agreement practices occurring in Yogyakarta. This study aims to determine why restrictions on land ownership for non-indigenous Indonesian citizens can occur and to analyze the judge’s decision on the nominee practice that occurred in the Yogyakarta High Court Decision Number 67/Pdt.G/2021/PT.YYK. The legal method used in this study is juridical-normative. The study of laws and regulations, legal theory, and court decisions as primary sources of law is the emphasis of normative legal research techniques. The research findings show that the Deputy Governor of DIY Instruction Letter Number 898/I/A/1975 and Law Number 13 of 2012 concerning the Special Status of DIY, Restrictions on land ownership for Indonesian Citizens (WNI) of descent in the Special Region of Yogyakarta (DIY) are a reflection of the dualism of the land law system in force in the Yogyakarta region, and the judge’s analysis in the Yogyakarta High Court Decision Number 67/Pdt.G/2021/PT.YYK, the Judge prioritizes the principle of substance over form, namely the actual substance of ownership based on evidence of transactions and control, not just the name on the certificate